Micromelum minutum Wight & Arn: Bioprospection Potency of Forest Conservation Area - Heri Suryanto (Buletin Eboni, 2020)
Bantimurung Bulusaraung National Park Area is one of the forest areas designated by the government as a conservation area in South Sulawesi. Optimization the use of the economic value of conservation areas and  potency of the biodiversity are many parties hope. Micromelum minutum Wight & Arn is one of the biodiversity richness in Bantimurung Bulusaraung National Park area. This plant predominantly contains flavonoid chemical compounds that are useful as antioxidants, antimicrobial, antibacterial, antiviral, anti-inflammatory, anti-allergic, anti-mutagenic, anti-clastogenic, anti-cancer, anti-platelet for humans.  M. minutum has potency as bioprospecting for Bantimurung National Park. The use of the conservation zone rehabilitation zones as wanafarma requires  plantcaracteristic and site management. M. minutum plantation should be placemented at river banks or create waterways if planting at dry land. In addition, efforts can be made to improve the physical properties of the soil in the form of loose and increased organic matter content by planting ground cover and fertilizing.